The impact of socio-religious beliefs and rural poverty on health care behavior: Case studies in the poor housing community in Kedah, Malaysia. - Abd Rahman, Saodah; Uddin, Md. Sayed (Morse Florse, 2018)
Numerous studies have found that health-seeking behavior depends on the individual\\\'s socio-cultural differences, demographic profiles, level of economic conditions, religiousness and religious affiliations, and the availability of health care providers. Existing literature indicates that health status and health behavior among poor and low-income groups was found to be very low and vulnerable under conditions. This study examines health status and health care seeking behaviors in households of a resettlement housing unit Kampung (village) Sadek founded by the Kedah Regional Development Authority (KEDA), in Kedah (North East state in Peninsular Malaysia), Malaysia. Total 21 households sampled were interviewed face to face using the random sampling procedure. The open-ended questionnaire was administered to cover the various issues, including the demographic and economic profile, health behavior and religiosity, to investigate the nature and extent of health care behavior by beneficiaries of resettlement in hospitals and alternative treatment (traditional and spiritual). The results showed that health resettlement recipients seeking behavior are shown to public hospitals / clinics and traditional healers. The results indicate that the respondents experienced the acute condition of poor health, suffered several types of diseases. Due to the numerous barriers to accessing modern health services, households were linked to traditional health providers (indigenous to nature consist primarily of two traditional providers such as bomoh and religious authority Imam). This article proposes few recommendations including hospitals/clinics should be incorporated near the resettlement area of housing because their majority of the means of transportation is on foot to visit public health service and KEDA authority must take an initiative, such as the mobile clinic services during the weekend so that in addition to poor people go the hospital / clinic rather the service comes to the poor.